Singing for Dr. King - Medearis, Angela Shelf 1956-; Van Wright, Cornelius (New York Scholastic, 2004)
change America by singing and marching for civil rights with Dr. Martin Luther King, Jr. Includes activity ideas for parents and children
Hurg
5
Keywords: Civil rights movements -- Fiction; Race relations -- Fiction